Integrating health care in Australia: a qualitative evaluation - Steven A. Trankle; Tim Usherwood; Penny Abbott; Mary Roberts; Michael Crampton; Christian M. Girgis; John Riskallah; Yashu Chang; Jaspreet Saini; Jennifer Reath (BMC, 2019)
Abstract Background With aging populations, a growing prevalence of chronic illnesses, higher expectations for quality care and rising costs within limited health budgets, integration of healthcare is seen as a solution to these challenges. Integrated healthcare aims to overcome barriers between primary and secondary care and other disconnected patient services to improve access, continuity and quality of care. Many people in Australia are admitted to hospital for chronic illnesses that could be prevented or managed in the community. Western Sydney has high rates of diabetes, heart and respiratory diseases and the NSW State Ministry of Health has implemented key strategies through the Western Sydney Integrated Care Program (WSICP) to enhance primary care and the outcomes and experiences of patients with these illnesses. Methods We aimed to investigate the WSICP's effectiveness through a qualitative evaluation focused on the 10 WSICP strategies using a framework analysis. We administered 125 in-depth interviews in two rounds over 12 months with 83 participants including patients and their carers, care facilitators, hospital specialists and nurses, allied health professionals, general practitioners (GPs) and primary care nurses, and program managers. Most participants (71%) were interviewed twice. We analysed data within a framework describing how strategies were implemented and used, the experiences around these, their perceived value, facilitators and barriers, and participant-identified suggestions for improvement. Results Care facilitators helped patients access services within the hospital and in primary care and connected general practices with hospital specialists and services. Rapid access and stabilisation clinics with their patient hotlines assisted patients and carers to self-manage chronic illness while connecting GPs to specialists through the GP support-line. Action plans from the hospital informed GPs and their shared care plans which could be accessed by other community health professionals and patients. HealthPathways provided GPs with local, evidence-based guidelines for managing patients. Difficulties persisted in effective widespread access to shared records and electronic communication across sectors. Conclusions The combined WSICP strategies improved patient and carer experience of healthcare and capacity of GPs to provide care in the community. Information sharing required longer-term investment and support, though benefits were evident by the end of our research.